A mini-review: photodynamic therapy-induced immune activation - Cai, Xiaowen; Leung, Albert Wing Nang; Lv, Le; Xu, Chuanshan (Frontiers in Pharmacology, 2026)
Tumors are considered to be among the most significant threats to human health. Immunotherapy, which is achieved through the body’s own immune response, shows great potential in the treatment of tumors. Nevertheless, the current low response rate in practical applications still needs to be overcome. Photodynamic therapy (PDT) is a minimally invasive treatment method that generates reactive oxygen species (ROS) through light irradiation of photosensitizers (PSs). It has been demonstrated that PDT is capable of not only efficiently eradicating tumors, but also effectively activating the immune system to recognize and destroy them. In addition, it has been demonstrated that the activation exhibits a persistent anti-tumor effect. It is evident that PDT demonstrates significant potential in the treatment of tumors, the inhibition of metastasis and the prevention of recurrence. This review summarizes the specific mechanisms of PDT-induced immune activation, including innate immunity and adaptive immunity, lists the relevant applications of organic and inorganic PSs in this field, and discusses the next challenges for PDT in tumor immunotherapy.